FORMATION AND DESCRIPTION OF THE WOMEN RIGHTS IN ISLAM - MM. Inagamova; N. Joraboev (American Journals Publishing, 2023)
The article deals with the issue of equality of women and men in the Islamic religion. The role of a woman in marriage, family responsibilities, relations between husband and wife, established rights and obligations regarding marriage and love are also analyzed.
Keywords: woman, man, marital relations, justice, equality, religion, integrity, family, law, duty, education, inheritance.